Malta : 2007 Article IV Consultation; Staff Report and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Malta's economic recovery is gaining traction, owing in large part to cyclical strength and some structural change. A public investment boom, financed largely by grants from the European Union, reignited growth in 2005. A modest recovery in exports and robust consumption growth, supported by rising employment and household borrowing, helped sustain the upswing in 2006. Although financial stability has continued to improve, the concentration of loan portfolios in real estate has continued to rise. Although nonperforming loans declined further, levels remain high and provisioning uneven.